Introduction to the Special Issue ‐ The internet, social media and trade union revitalization: Still behind the digital curve or catching up?. (21st August 2021) - Geelan, Torsten
Abstract: This article introduces the special issue of New Technology, Work and Employment titled "The Internet, Social Media and Trade Union Revitalization: Still Behind the Digital Curve or Catching Up?" The objectives of this special issue are threefold. First, to develop an analytical framework that can help researchers assess the role that internal and external factors play in mediating the nature and scope of union experimentation with new information and communication technologies (ICTs) and its contribution to the outcomes of revitalisation. Second, to present methods and concepts that are new to this area of research. Third, to generate empirical insight into how the various actors that constitute the trade union movement (e.g. worker councils, union confederations, trade unions, and union‐led coalitions) can and are using the internet, social media and artificial intelligence as a means of revitalisation. Taken together the geographical scope of the articles range from single‐country cases studies in Germany, the UK and Canada, to a cross‐national case study in Australia and the USA, and a comparative study across Europe. In terms of ICTs, attention is given to websites, Twitter, Facebook, YouTube and an AI chatbot.